The aporia of rights explorations in citizenship in the era of human rights - Yeatman, Anna 1948- (Bloomsbury, 2014)
"The Aporia of Rights is an exploration of the perplexities of human rights, and their inevitable and important intersection with the idea of citizenship. Written by political theorists and philosophers, essays canvass the complexities involved in any consideration of rights at this time. Yeatman and Birmingham show through this collection of works a space fora vital engagement with the politics of human rights"..
Includes bibliographical references and index
Keywords: PHILOSOPHY / Political; POLITICAL SCIENCE / Political Freedom & Security / Human Rights; POLITICAL SCIENCE / Civics & Citizenship; Menschenrecht; Human rights; Citizenship; Staatsangehörigkeit; Aufsatzsammlung